Importance of topography and soil physical properties on the growth of shorea macrophylla under reforestation at Sampadi Forest Reserve - Nur Hanani Hanis, binti Mohd Nawar (Universiti Malaysia Sarawak (UNIMAS), 2012)
Shorea macrophylla are characterised as one of the Dipterocarp indigenous trees that exhibit a fast growing ability. This species is said to be favourable on clay riparian alluvium and locally abundant on damp soil on hillside by river and streams habitat. Several studies reported that S. macrophylla is less favourable to ridge tops and upper slopes of a hill. Their growth patterns findings are very important, as this species is commonly used in reforestation plantation, especially in Sarawak. In this study, the relationship between soil physical properties at various topographical conditions were analyzed in the respect of the growth of S. macrophylla planted in reforestation area of Sampadi Forest Reserve, Sarawak. Study plots with the size of 50 m x 50 m were constructed at reforestation areas planted with S. macrophylla at various age stands from 1996 (SM96), 1997 (SM97) and 1998 (SM98). In each study plots, a topographical map was constructed by using the conventional method. By referring to the constructed maps, soil samples were collected at 0 - 10 cm and 30 - 40 cm depths from several random points within each contour zone for soil physical analysis. Soil physical analysis involved in this study includes soil texture analysis, bulk density, porosity, water content, moisture content and compaction. The findings showed that in relation between soil physical properties and topographical characteristics, S. macrophylla shows strong adaptability across all range of elevation and other soil physical properties. However, the presence of stagnant water and interruption of pioneer species in between the planting lines greatly resulted in poor growth performance and survivability of S. macrophylla.